FOUR-YEAR INTEGRATED TEACHER EDUCATION PROGRAMME PROPOSED BY NATIONAL EDUCATION POLICY 2020: AN ANALYTICAL STUDY - Surjan, Praveen Kumar; Chandoria, Virender Kumar; Singh, Pooja (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The National Education Policy 2020 of India marks a significant shift in the way we view and understand teacher education. The study reflects the need for high-quality, multidisciplinary and holistic teaching-training, with a special emphasis on the need for high-quality, multidisciplinary and holistic teaching-training. The cornerstone of this reform in the Indian education system is the introduction of the Integrated Teacher Education Programme (ITEP). The present study explores the Integrated Teacher Education Programme (ITEP) and analyses its objectives, features, structure and potential impact on the Indian education system. The aim of the ITEP is to enhance teacher quality by integrating broad subject knowledge with pedagogical skills, thereby producing teachers who are well equipped to meet the diverse needs of contemporary classrooms. The present study outlines the key components of the Integrated Teacher Education Programme, which includes a strong curriculum that combines content knowledge, elective courses and professional education elements. Practical training through internships and teaching practicums forms an important part of the programme, bridging the gap between theoretical knowledge and classroom application. The programme emphasises continuous assessment and professional development to ensure continuous improvement and adaptation of teaching methods and techniques. The potential impact of ITEP is significant, as it appears committed to improving teaching effectiveness, promoting inclusive education, and fostering innovative pedagogical approaches. By standardizing teacher education and setting common quality benchmarks, ITEP aims to eliminate inequities and enhance the overall quality of education across India. The program also focuses on preparing teachers to leverage educational technology, adopt experiential learning methods, and implement inclusive education practices, thus aligning with the broader goals of the National Education Policy 2020. However, the presented study also identifies several challenges in the implementation of ITEP which are discussed in detail in the study.